Neuroplasticity — Exercise-Induced Response of Peripheral Brain-Derived Neurotrophic Factor: A Systematic Review of Experimental Studies in Human Subjects - Knaepen, Kristel; Goekint, Maaike; Heyman, Elsa Marie; Meeusen, Romain (Sports medicine (Auckland), 2010)
Exercise is known to induce a cascade of molecular and cellular processes that support brain plasticity. Brain-derived neurotrophic factor (BDNF) is an essential neurotrophin that is also intimately connected with central and peripheral molecular processes of energy metabolism and homeostasis, and could play a crucial role in these induced mechanisms. This review provides an overview of the current knowledge on the effects of acute exercise and/or training on BDNF in healthy subjects and in persons with a chronic disease or disability. A systematic and critical literature search was conducted. Articles were considered for inclusion in the review if they were human studies, assessed peripheral (serum and/or plasma) BDNF and evaluated an acute exercise or training intervention. Nine RCTs, one randomized trial, five non-randomized controlled trials, five non-randomized non-controlled trials and four retrospective observational studies were analysed. Sixty-nine percent of the studies in healthy subjects and 86%of the studies in persons with a chronic disease or disability, showed a ‘mostly transient’ increase in serum or plasma BDNF concentration following an acute aerobic exercise. The two studies regarding a single acute strength exercise session could not show a significant influence on basal BDNF concentration. In studies regarding the effects of strength or aerobic training on BDNF, a difference should be made between effects on basal BDNF concentration and training-induced effects on the BDNF response following an acute exercise. Only three out of ten studies on aerobic or strength training (i.e. 30%) found a training-induced increase in basal BDNF concentration. Two out of six studies (i.e. 33%) reported a significantly higher BDNF response to acute exercise following an aerobic or strength training programme (i.e. compared with the BDNF response to an acute exercise at baseline). A few studies of low quality (i.e. retrospective observational studies) show that untrained or moderately trained healthy subjects have higher basal BDNF concentrations than highly trained subjects. Yet, strong evidence still has to come from good methodological studies. Available results suggest that acute aerobic, but not strength exercise increases basal peripheral BDNF concentrations, although the effect is transient. From a few studies we learn that circulating BDNF originates both from central and peripheral sources. We can only speculate which central regions and peripheral sources in particular circulating BDNF originates from, where it is transported to and to what purpose it is used and/or stored at its final destination. No study could show a long-lasting BDNF response to acute exercise or training (i.e. permanently increased basal peripheral BDNF concentration) in healthy subjects or persons with a chronic disease or disability. It seems that exercise and/or training temporarily elevate basal BDNF and possibly upregulate cellular processing of BDNF (i.e. synthesis, release, absorption and degradation). From that point of view, exercise and/or training would result in a higher BDNF synthesis following an acute exercise bout (i.e. compared with untrained subjects). Subsequently, more BDNF could be released into the blood circulation which may, in turn, be absorbed more efficiently by central and/or peripheral tissues where it could induce a cascade of neurotrophic and neuroprotective effects.